2007
DOI: 10.1515/jpem.2007.20.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Use of Continuous Subcutaneous Insulin Infusion Compared with Multiple Daily Injections of Glargine in Pediatric Patients

Abstract: Background: Studies comparing continuous subcutaneous insulin infusion (CSII) and glargine in pediatric patients are scarce and cover only 1 year follow up. Although short-term results are favorable for CSII, there is no clear evidence whether this therapy leads to a sustained improvement of glycemic control. Objective: To evaluate long-term effects and safety of CSII versus multiple daily injections (MDI) of glargine over 2 years of treatment in children and adolescents.Patients and Methods: 32 patients (aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 2 publications
0
13
0
1
Order By: Relevance
“…Pickup et al (2006) 139 reported that 37% of CSII subjects and 13% of MDI ones achieved HbA 1c < 7%; for a target of < 8%, the proportions were 73% and 30%. Radermecker et al (2005) 143 noted that of 95 patients on CSII, only five reached HbA 1c of 7% or less; most (66) 167 (n = 8) the increases of 0.01% and 0.08%, respectively, were neither clinically or statistically significant. The statistical significance level was not reported in Variety of reasons for discontinuing pumpusually multiple reasons; including, dislike or difficulty with needle insertion (n = 3), insurance difficulties (n = 2), trouble keeping the infusion site clean (n = 2), tape not adhering (n = 2) and general dislike of the pump (n = 2) Reasons for discontinuing: major problems (n = 8, DKA, insulin omission); diabetes burnout (n = 8); minor problems (n = 6, infusion site problems), body image concerns (n = 4); concerns about weight gain (n = 3) 3.8 years 159 (n = 12), where the increase was 0.6%.…”
Section: Glycaemic Control As Reflected In Hba 1cmentioning
confidence: 98%
See 3 more Smart Citations
“…Pickup et al (2006) 139 reported that 37% of CSII subjects and 13% of MDI ones achieved HbA 1c < 7%; for a target of < 8%, the proportions were 73% and 30%. Radermecker et al (2005) 143 noted that of 95 patients on CSII, only five reached HbA 1c of 7% or less; most (66) 167 (n = 8) the increases of 0.01% and 0.08%, respectively, were neither clinically or statistically significant. The statistical significance level was not reported in Variety of reasons for discontinuing pumpusually multiple reasons; including, dislike or difficulty with needle insertion (n = 3), insurance difficulties (n = 2), trouble keeping the infusion site clean (n = 2), tape not adhering (n = 2) and general dislike of the pump (n = 2) Reasons for discontinuing: major problems (n = 8, DKA, insulin omission); diabetes burnout (n = 8); minor problems (n = 6, infusion site problems), body image concerns (n = 4); concerns about weight gain (n = 3) 3.8 years 159 (n = 12), where the increase was 0.6%.…”
Section: Glycaemic Control As Reflected In Hba 1cmentioning
confidence: 98%
“…Among adults and mixed age groups, planning for pregnancy or during pregnancy [140][141][142][143] 164 minimum duration of diabetes 167,168 and daily insulin requirement of more than 0.75 units/kg. 167 One study reported that patients were excluded if in the honeymoon phase.…”
Section: Reasons For Starting Csiimentioning
confidence: 99%
See 2 more Smart Citations
“…In the era of soluble long-acting analogs, MDI is no longer inferior to CSII in terms of A1C and frequency of hypoglycemia (73)(74)(75)(76). CSII has the theoretical advantage of lower variability compared with MDI, but so far this has been difficult to prove.…”
Section: Regimens Of Multiple Daily Injections Andmentioning
confidence: 99%